Pengenalan Wirausaha Sejak Dini Pada Anak melalui Pengolahan Salad Buah - Lubis, Desy Irana Dewi; Siregar, Ade Rahma Ayu; Octaviana, Dina; Fathimah, Vidya (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Introducing entrepreneurship at an early age will provide children with the knowledge that the goods being sold are not simply made out of thin air. There is a process involved in transforming raw materials into finished goods and calculating the profit from the goods sold. This activity was carried out at the Pondok Tahfiz Qur’an Al Luqman, Riwayat I Road Gg. Tower, Patumbak District, Deli Serdang Regency, North Sumatra. The method used in this community service activity is Participatory Action Research (PAR), allowing participants to directly engage in the production process. The aim of this activity is to instill an entrepreneurial spirit in children from an early age and enable them to recognize raw materials that can be processed into marketable products. The target is for children to gain new knowledge about processing raw materials into finished products and how to package them. The outcome of the community service activity is that the children learned about fruit salad processing and how to market their products.